Functional role of proprioceptive feedback in balance and in reactive movement - Gollhofer, A. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Human movement is generated either by internal muscle forces, or by external forces that are attached to the body system. Most of our muscles act via lever arms on the bone system, thus generating rotational forces that produce consequently torques and joint moments. Therefore, studies dealing with control strategies of joint moments to achieve a desired movement or an intended task are addressing one of the most interesting topics. In several papers the constraints and relative importance of sensory feedback are investigated. It seems that in a given task a complex interaction of feed-forward- and feed-back-mechanisms adjust the actual joint stiffness. By means of the H-reflex methodology, the spinal excitability for muscles can be determined. Under selective conditions, the inhibitory or facilitatory behavior of spinal reflex contribution can be investigated. Quite recently, the transcranial magnetic stimulation (TMS) has been developed to assess corticospinal excitability during human movement. Selective stimulation of the neurons in the motor cortex allows the determination of the relative contribution of corticospinal activation during movement. Application of both techniques, H-reflex and TMS, allows differentiation of spinally and centrally organized muscle activation. The present paper highlights recent findings about neuromuscular control in balance and stretch-shortening cycle movements and reflects adaptations induced by balance training. For both type of movements, the stiffness properties of the involved joint complexes are modulated by spinal and central modulation of the neuromuscular activation. Training adjusts/adapts this motor control specifically for balance tasks and for reactive movements. Longitudinal training studies in which postural control (balance training) was exercised showed that the spinal and the cortical contributions were reduced after the training. Thus it was assumed that motor control was shifted towards supraspinal centers (Taube et al. 2007). From stretch shortening cycle (SSC) it is known that high muscular stiffness is a prerequisite to enable proper performances and that feed-forward activation of the extensor muscles prior to ground contact is modulated by effective stretch reflex contributions (feed-back activation). This modulation, however, is largely dependent on the individual stretch load tolerance of the neuromuscular system. Recent results indicate that the "stereotyped" reflexes are much more modulated than expected previously. It has been shown that modulation of spinal circuitry is achieved by presynaptic inhibition.